Strategies and possible directions to improve Technology Scouting in China - Wolfgang Renninger; Mirjam Riesemann (Hochschule für angewandte Wissenschaften Amberg-Weiden (HAW), 2010)
This paper examines how theoretical and cultural dimensions in China challenge the use of the generic Open-Market Innovation model by companies in general and one sample Company in China in particular. To carry this analysis out, several interviews with venture technologists and innovators of a company in China were conducted and results are concluded out of business case studies. The outcome of these analyses shows that an Open-Market Innovation Company in China is constrained to a certain degree by political and cultural challenges. Nonetheless, the importance of the Chinese market makes a strong argument for developing an effective business model for China. Therefore, this article concludes that the focus going forward must be on seeking opportunities to improve Technology Scouting in China. – – Die Tendenz, vermehrt auch Innovationen außerhalb der eigenen Firma zu finden, steigt. Dieser Artikel beschreibt Probleme und Herausforderungen des OpenMarket Innovation Modells in China. Die Ursachen wie auch Probleme wurden mit Hilfe verschiedener Analysemethoden ermittelt, wofür Führungskräfte des Innovationsmanagements aus einem multinationalen Konzern in China befragt wurden. Das Resultat belegt, dass ein Open-Market Innovation Modell in China sehr viel schwieriger durchzuführen ist verglichen zu westlichen Ländern. Nichts desto trotz ist der chinesische Markt ein wichtiger Weltmarkt, der Potential für Verbesserungen bereitstellt und für dieses Modell spricht. Kritische Erfolgsfaktoren zeigen Möglichkeiten auf, mit denen Technology Scouting in China erleichtert werden kann.
Keywords: A22; A23; 330; E-Learning; LMS; Hype-Cycle; Nachhaltigkeit; IT-Strategie